Desenvolvimento funcional da codificação da fala por meio da representação do frequency-following response em lactentes - Ferreira, Laís (2019)
This work presents a research regarding the effect of auditory maturation in the encoding process of speech sounds during the first 45 days of life and in the investigation of the influence of the congenital toxoplasmosis on the neurophysiological responses of Frequency-Following Response in infants. A total of 95 normal hearing infants were included in the study, of which 87 were healthy infants with no Risk Indicators for Hearing Impairment and oito with congenital toxoplasmosis. The research procedure was the Frequency-Following Response recorded using the Smart Ep module of Intelligent Hearing Systems® (IHS). The syllable [da], of 40ms long, was presented in 80dBnHL, monaural in the right ear. The following data were obtained for the time domain analysis: absolute latencies and amplitudes of V, A, C, D, E, F and O waves, measurement between onset (A) and offset (O) and slope measurement. To measure the effect of maturation of the auditory pathway during the first 45 days of life of the infant, the sample of 80 healthy infants was divided into three groups: Group I (0 to 15 days), Group II (16 to 30 days) and Group II (31 to 45 days). To investigate the influence of congenital toxoplasmosis on the Frequency- Following Response, the sample of 20 infants was divided into two groups: Group with congenital toxoplasmosis: 8 subjects diagnosed with congenital toxoplasmosis and Control group: 12 healthy infants. Regarding the effect of auditory maturation, the results indicated an increase in the latency of all the FFR waves with the advancing of age, being statistically significant differences for V (<0.001 *), A (<0.001 *), E (<0.001 *), F (<0.001 *) and O (<0.001 *). The mean values of the amplitude variable showed a statistically significant difference for the wave V (p = 0.010 *). The slope measurement (<0.001 *) increased in the course of the 45 days of life. For the influence of the congenital toxoplasmosis, the results indicated that infants with congenital toxoplasmosis presented increased latency of all Frequency-Following Response waves, with a statistically significant difference in the waves V (p = 0.046 *), A (p = 0.017) E (p = 0.011 *), F (p = 0.044 *) and O (p = 0.018 *) and decreased amplitude for wave A (p = 0.003 *). In addition, infants with congenital toxoplasmosis present a slope reduction (0.001 *) and higher values for the measurement A-O (0.030 *). From these data, this study allows to conclude that the encoding process of speech sounds undergoes the effects of auditory maturation during the first 45 days of the infant´s life. And that infants with congenital toxoplasmosis present a disorganization in the neural encoding of speech sounds. Thus, this research strengthens the clinical relevance of the Frequency-Following Response in the infant population as it demonstrates that the physiological modifications involved in the maturation process of the auditory pathway can be measured by this potential and that the Frequency-Following Response can be a useful tool in the evaluation of infants at risk for language disorders.